Non-traumatic scapholunate dissociation in a 10-year-old female: A case report - Bandinelli, Diletta; Pagnotta, Alessia; Pieracci, Edoardo Maria; Basiglini, Luca; Aulisa, Angelo Gabriele (Frontiers in Surgery, 2022)
Introduction Severe or minor repetitive trauma, inflammation, infection, tumors, and congenital ligamentous laxity have been etiologically implicated in scapholunate dissociation (SLD). While a few cases of patients with asymptomatic SLD have been reported in the literature, despite radiographically demonstrated widened scapholunate angles and rotatory subluxation of the scaphoid bone, these patients experienced only mild or no pain and no dorsal intercalated segment instability deformity. Here, we report the case of a monolateral non-traumatic SLD in a young 10-year-old girl that led to an important range of motion impairment with no wrist pain. The case represents a rarity for no previous history of trauma, young age, and no pain. Main symptoms and important clinical findings In our patient, an examination revealed a reduced range of motion in the left wrist and no pain during passive or active mobilization. The X-ray showed a 16 mm scapholunate gap in the anteroposterior roentgenogram. In this case, we suggested that congenital or developmental ligamentous laxity may be the cause of SLD. The diagnostic assessment was completed with a wrist MRI and CT. Therapeutic interventions and outcomes The patient underwent an open dorsal surgery: we directly reduced the dislocated bones and fixed them with five percutaneous 1 mm k-wires. Finally, the scapholunate ligaments were repaired using bone-absorbable anchor sutures. The wrist was immobilized in a volar cast for 8 weeks. The patient was able to resume her daily life activities (included sport) within 12 months. Conclusion Carpus injuries are rare in children, and treatment, especially for young-age patients, is fraught with risks and remains controversial. Our case demonstrates that the patient has had a good clinical outcome. The physio-rehabilitation program for this patient has been of long duration. Most previous studies have shown excellent clinical results after an average of 2.4 years.